PENGARUH LUAS LAHAN PERTANIAN DAN BIAYA PEMELIHARAAN TERHADAP PENDAPATAN PETANI (STUDI KASUS DESA KEPENUHAN RAYA) - Hamdi Sari Maryoni (Jurnal Ilmiah Cano Ekonomos, 2017)
The purpose of this study was to identify the Influence of Land Area, Maintenance Costs, Revenues and Number of Families Against Rural Farmers Fullness Kingdom. Research methods through direct observation and interviews with the instrument a questionnaire containing open questions to the respondents in the study area with multiple linear regression analysis. The result, it was concluded that the higher the land area, cost of care, and the number of families of respondents, the higher the income earned. Variable maintenance costs and land area significantly affect the income of farmers with significant value (0.00), but the number of families do not significantly affect the income of farmers with a significance value (0.051).